Gender role moderates correlation between learning needs and behavioural intention of sexual health care in female nurses. Issue 5 (11th March 2021) - Huang, Cheng‐Yi; Lee, Shu‐Hsin; Wu, Tzu‐Jung; Sun, Yu‐Ching; Tsai, Li‐Ya
Abstract: Aim: This study evaluated the correlation between learning needs and behavioural intention of sexual health care in female Registered Nurses and to assess the moderating effect of gender role on this relationship. Design: In this cross‐sectional questionnaire‐based survey, a convenience sampling of female Registered Nurses was included from Chung Shan Medical University Hospital, Taiwan. Methods: Three questionnaires were used to obtain self‐reported data on learning needs, behavioural intention and gender role. Results: Based on gender role scores, 11.8% of participants were feminine, 10.0% were masculine, 31.0% were androgynous and 47.2% were undifferentiated. Significant positive correlations between learning needs and behaviour intention were observed in the total population as well as in undifferentiated, feminine and androgynous nurses (all p < .05). Learning needs were positively associated with the behavioural intention of sexual health care in female nurses, which was moderated by gender role ( F = 2.868, p = .036).